Peran Sistem Informasi Akademik (SIA) Berbasis Turnitin Dalam Pengendalian Kecurangan Akademik Di Program Pascasarjana Universitas Muhammadiyah Mamuju - Nur Khaila Anugra Maryam (Jurnal Ilmu Manajemen dan Akuntansi Nusantara, 2026)
The development of information technology has encouraged educational institutions to integrate digital systems into the management of academic activities. One of the systems that has begun to be implemented is Turnitin as a plagiarism detection tool in the Academic Information System (AIS). This article aims to analyze the role of Turnitin-based AIS in controlling academic cheating, particularly in the Postgraduate Program at Muhammadiyah University. The method used is a literature study from journals, books, and other scientific sources. The results of the analysis show that the integration of Turnitinin the AIS can help improve academic integrity, reduce the potential for plagiarism, strengthen an ethical research culture, and facilitate the academic verification process by lecturers and faculty administrators. This article concludes that the implementation of Turnitin in campus information systems has the potential to be a strategic solution in creating transparent, efficient, and high-quality academic governance.